Van der Waals integration of mixed-dimensional CeO2@Bi heterostructure for high-performance self-powered photodetector with fast response speed. Issue 43 (27th October 2022) - Liu, Xinlin; Liu, Cailing; Fu, Yushuang; Xu, Yiguo; Khan, Karim; Tareen, Ayesha Khan; Zhang, Ye
Abstract : CeO2 @Bi van der Waals heterostructure has been utilized for photoelectrochemical-type photodetector. The photodetector shows self-powered photodetection with fast response speed and good long-term cycle stability in 1.0 M KOH electrolyte. Abstract : Heterostructures have been extensively investigated for optoelectronic devices owing to their fantastic physicochemical properties. Herein, a mixed-dimensional van der Waals heterostructure (vdWH) CeO2 @Bi, 1D ceria (CeO2 ) loaded with 0D bismuth quantum dots (Bi QDs), is synthesized through a facile hydrothermal bottom-up method. It is found that the fabricated CeO2 @Bi-based photoelectrochemical (PEC)-type photodetector (PD) shows self-powered photodetection capability with a fast photoresponse speed of 0.02 s. Besides, a photocurrent of 2.00 μA cm −2 and a photoresponsivity of 888.89 μA W −1 under 365 nm illumination are obtained. Furthermore, good long-term cycle stability is also observed after 1 month in a harsh environment, indicating the great potential for practical applications. These results are further supported by density functional theory (DFT) calculations. We believe that the presented work is expected to provide a new pathway for the future utilization of vdWHs for high-performance optoelectronics.